Fillettes et garçonnets dans les pratiques rituelles du monde grec de l’époque classique à l’époque impériale - Sophie Laribi-Glaudel (Genre & Histoire)
In the Ancient Greek world, as soon as they were born and during their first seven years of life, i.e. early childhood, girls and boys were the subjects of a several rituals documented by literature, iconography and epigraphy since the Archaic Period. The aim of these rituals was to integrate them into their family and into the civic community which they were part of, and to protect them from the dangers of early childhood, a period during which the infant mortality rate was very high. These rituals also contributed to assigning a gender to them, female or male, and to make them conform to the gendered expectations of the societies of the Ancient Greek world.